The Effect of the Outing Class Method on the Naturalist Intelligence of Children Aged 5-6 Years - Lia Roaina; Ahmad Syukri Sitorus (Universitas Islam negeri Mahmud Yunus Batusangkar, 2025)
Naturalist intelligence is a fundamental domain of early childhood development, reflecting children's capacity to observe, identify, and relate to elements of the natural world an ability that is increasingly essential in fostering ecological consciousness from an early age. This study aims to determine the effect of the outing class learning method on the naturalist intelligence of children aged 5-6 years. The research employed a Quasi-Experimental Design. Participants consisted of 20 children from Group A and Group B at Rahmatul Iman II Kindergarten. Using simple random sampling, ten children were assigned to the control group (Group A) and ten to the experimental group (Group B). Data were collected through structured observation to assess indicators of naturalist intelligence. Data analysis included both descriptive and inferential statistics, namely normality tests, homogeneity tests, and independent t-tests. The findings revealed a statistically significant difference between the experimental and control groups, with the experimental group showing a more substantial improvement in naturalist intelligence. The analysis confirmed this outcome, as the calculated t-value was substantially higher than the critical value, leading to the rejection of the null hypothesis. It can thus be concluded that the outing class method has a significant and positive impact on the development of naturalist intelligence in children aged 5-6 years. These findings imply that integrating experiential outdoor learning into early childhood education may serve as an effective approach to nurturing environmental sensitivity and holistic development.